1991
DOI: 10.1002/eji.1830210331
|View full text |Cite
|
Sign up to set email alerts
|

Unusual phenotype of intestinal intraepithelial lymphocytes in the rat: predominance of T cell receptor α/β+/CD2 cells and high expression of the RT6 alloantigen

Abstract: The phenotype of intraepithelial lymphocytes (IEL) from the small intestine of adult rats was studied by flow cytometry. Using appropriate monoclonal antibodies the expression patterns of the T cell receptor alpha/beta (TcR2), CD2, the alloantigen RT6 and several other T cell antigens were analyzed. The vast majority of rat IEL expressed TcR2 which is in contrast with data reported for the mouse. The comparison of IEL with lymph node cells revealed major phenotypic differences. Whereas CD2 was present on virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…IEL comprised both CD3 þ and CD3 ¹ subpopulations, with most of the CD3 þ cells expressing a/b TCR. The CD8aa þ and CD8ab þ subsets were predominant in 2-month-old animals, while CD4 þ IEL (mostly coexpressing CD8a) constituted large numbers by 6 months, corroborating earlier data [6][7][8]22].…”
Section: Iel Phenotypes Differ Between Jejunum and Ileumsupporting
confidence: 89%
See 1 more Smart Citation
“…IEL comprised both CD3 þ and CD3 ¹ subpopulations, with most of the CD3 þ cells expressing a/b TCR. The CD8aa þ and CD8ab þ subsets were predominant in 2-month-old animals, while CD4 þ IEL (mostly coexpressing CD8a) constituted large numbers by 6 months, corroborating earlier data [6][7][8]22].…”
Section: Iel Phenotypes Differ Between Jejunum and Ileumsupporting
confidence: 89%
“…Most information concerning the phenotypes of rat IEL have been obtained by flow cytometric analysis of dispersed cells [6][7][8]22]. The present study was undertaken to determine the distribution of IEL phenotypes in situ.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic composition of IEL appears to be influenced by both genetic and environmental factors (8). Most IEL are CD8ϩ, and include cells bearing T cell receptors (TCR) composed of ␥␦ and especially ␣␤ chains (10,11). In addition to the peripheral classic phenotypes [CD8ϩCD4 -and CD8 -CD4ϩ], some IEL exhibit the CD8ϩCD4ϩ (DP) and the CD8 -CD4 -(DN) …”
mentioning
confidence: 99%
“…At these ranges, the RT-PCR technique is much more accurate and is more likely to pick up differences in transcript levels. The decrease in RT6 and integrin ␣ E transcripts gives a good indication that IEL are affected, since it has been shown that IEL express RT6 and integrin ␣ E to a much greater extent than lamina propria lymphocytes (6,9,40). The results may also allow a tentative identification of the type of IEL affected.…”
Section: Cd8mentioning
confidence: 99%
“…Because of their strategic positioning, making up the first line of defense together with the epithelial cells, they are proposed to play an important role in mucosal immunity in relation to both immune defense and intestinal homeostasis (13,44). One problem in studying IEL is the lack of a specific cell marker, although it is known that the cell surface protein RT6, restricted to mature T lymphocytes and a subpopulation of natural killer cells, is expressed at a remarkably high density on IEL (9). In addition, integrin ␣ E seems to be a promising marker for IEL, although expression has also been detected on other T-cell subsets (2,6).…”
mentioning
confidence: 99%